A new bromelain-based enzyme for the release of Dupuytren’s contracture: Dupuytren’s enzymatic bromelain-based release - Rubin, G. (Bone Joint Res, 2016)
OBJECTIVES: Injectable Bromelain Solution (IBS) is a modified investigational derivate of the medical grade bromelain-debriding pharmaceutical agent (NexoBrid) studied and approved for a rapid (four-hour single application), eschar-specific, deep burn debridement. We conducted an ex vivo study to determine the ability of IBS to dissolve-disrupt (enzymatic fasciotomy) Dupuytren’s cords. MATERIALS AND METHODS: Specially prepared medical grade IBS was injected into fresh Dupuytren’s cords excised from patients undergoing surgical fasciectomy. These cords were tested by tension-loading them to failure with the Zwick 1445 (Zwick GmbH & Co. KG, Ulm, Germany) tension testing system. RESULTS: We completed a pilot concept-validation study that proved the efficacy of IBS to induce enzymatic fasciotomy in ten cords compared with control in ten cords. We then completed a dosing study with an additional 71 cords injected with IBS in descending doses from 150 mg/cc to 0.8 mg/cc. The dosing study demonstrated that the minimal effective dose of 0.5 cc of 6.25 mg/cc to 5 mg/cc could achieve cord rupture in more than 80% of cases. CONCLUSIONS: These preliminary results indicate that IBS may be effective in enzymatic fasciotomy in Dupuytren’s contracture. Cite this article: Dr G. Rubin. A new bromelain-based enzyme for the release of Dupuytren’s contracture: Dupuytren’s enzymatic bromelain-based release. Bone Joint Res 2016;5:175–177. DOI: 10.1302/2046-3758.55.BJR-2016-0072.